What the genome sequence is revealing about trypanosome antigenic variation. - Barry, J D; Marcello, L; Morrison, L J; Read, A F; Lythgoe, K; Jones, N; Carrington, M; Blandin, G; Böhme, U; Caler, E; Hertz-Fowler, C; Renauld, H; et al. (Biochem Soc Trans, 2005)
African trypanosomes evade humoral immunity through antigenic variation, whereby they switch expression of the gene encoding their VSG (variant surface glycoprotein) coat. Switching proceeds by duplication of silent VSG genes into a transcriptionally active locus. The genome project has revealed that most of the silent archive consists of hundreds of subtelomeric VSG tandem arrays, and that most of these are not functional genes. Precedent suggests that they can contribute combinatorially to the formation of expressed, functional genes through segmental gene conversion. These findings from the genome project have major implications for evolution of the VSG archive and for transmission of the parasite in the field.
Keywords: Animals; Antigens, Protozoan; Evolution, Molecular; Genetic Variation; Genome; Trypanosomatina; Variant Surface Glycoproteins, Trypanosoma